2010
DOI: 10.4049/jimmunol.0904192
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Peripheral Blood T, B, and NK Cells during a Menstrual Cycle of Normal Healthy Women

Abstract: Cyclical hormonal changes during an ovarian cycle may affect immune responses, which is crucial for the embryonic implantation. We aim to investigate whether the levels and activity of T, B, and NK cells change during a menstrual cycle. Twenty-two normally cycling women were enrolled and peripheral blood was drawn serially during a menstrual cycle. Intracellular cytokine expression of CD3+CD4+ and CD3+CD8+ cells, and Th1/Th2 cytokine-producing T cell ratios were determined using flow cytometric analysis. NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
3
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 45 publications
2
83
3
5
Order By: Relevance
“…In this case, one could expect the increase in IFN-g production by female cells due to enhanced T h 1 responses due to low level of estrogen [8]. However, according to Lee et al, percentages of T H 1/T H 2 cytokine-producing T cells do not change significantly throughout cycle [36]. Faas et al [37] also have shown that intracellular levels of IFN-g, IL-2 or IL-10 do not vary between the phases of the ovarian cycle.…”
Section: Discussionmentioning
confidence: 93%
“…In this case, one could expect the increase in IFN-g production by female cells due to enhanced T h 1 responses due to low level of estrogen [8]. However, according to Lee et al, percentages of T H 1/T H 2 cytokine-producing T cells do not change significantly throughout cycle [36]. Faas et al [37] also have shown that intracellular levels of IFN-g, IL-2 or IL-10 do not vary between the phases of the ovarian cycle.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the estradiol/progesterone balance during the menstrual cycle can mediate immunity and have an impact on the proportions of B and T lymphocytes [31,32]. It might also have an impact on their mitotic behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…low statistical power of the study. In comparison to other studies on immunological fluctuations in relation to the menstrual cycle and use of CHC, earlier studies have both smaller (54,87) and larger (57) sample sizes.…”
Section: Immunological Assaysmentioning
confidence: 90%
“…Indeed, previous studies indicated estrogenic effect on T cell number during normal menstrual cycles (87) and during CHC cycles (93). Therefore, our approach of using CD3E…”
Section: Immunological Assaysmentioning
confidence: 96%